Pengembangan Kapasitas Mantan Pekerja Seks Komersial Dalam Peningkatan Fungsi Sosial Oleh Lembaga Kharisma Palembang - Wahidin Wahidin; Mulyanto Mulyanto; Dadang Hikmah Purnama (Jurnal Empirika, 2018)
The purpose of this Research was to analyze three aspects of capacity building of former commercial sex workers in improving social function by charisma institutions, including capacity building processes, capacity building forms and capacity building strategies. In general, capacity building is a learning in enhancing capability, skills and increasing mastery possessed by an individual, group or organization, carried out by social welfare institutions in organizing various types of activities, especially those directly related to the empowerment of former commercial sex workers. This Research uses a qualitative approach. The object of this case study research is the Kharisma Institute in carrying out capacity building activities for former commercial sex workers. The source of the data in this research came from primary data sources, namely key informants of the kharisma institution, companion, former commercial sex workers, some of social service employees also became supporting informants of this research. Secondary data from various literature departments. Data collection techniques use the method of observation (observation), interviews (interviews), and documentation. The results of the research provide an overview of the aspects of the process, forms and strategies for improving the social function of former commercial sex workers, after participating in activities they have knowledge, high social life, have the ability to be entrepreneurial, confident, and able to build social relations.